(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Fiber optic network architectures can be classified into two broadcategories: broadcast and select, and wavelength routing architectures. Inbroadcast and select architectures, different nodes broadcast messages ondifferent WDM channels, typically, over passive star, linear bus, or treetopologies. Access nodes in these networks route the messages. In contrast,wavelength routing networks employ active switches to route messages based onthe wavelengths and thus messages carried in optical domain "as far aspossible". Today, broadcast topologies are used for LAN/MAN solutionsbecause they are simple to construct and cost effective. Networking has becomean integral part of computing. Computing applications in all sectors are nowdependent upon computer networks to routinely, accurately and rapidly conveydata from one to another. Similarly, networking is the heart of audio and videocommunications.